(untitled) (Tempo e Argumento, 2021)
Río Abajo, a work released by the Colombian artist Erika Diettes in 2008, brings up an encounter with grief faced by the relatives of missing people who have been thrown into the Colombian rivers. The work consists of a series of photographs of clothing, floating in water, which belonged to the victims, immersing us in a world full of real ghosts where the temporal and spatial constraints that delimit the world of the living are stretched and establish a painful but necessary dialogue in a society that tends to forgetfulness and anesthesia. Herein there is an approach from aesthetics and philosophy to this work, in a land – Colombia – where talking about missing people is a political act. Keywords: Erika Diettes; armed conflict in Colombia; missing people; history of the present time; aesthetic device; phantasmagoria.